Adipose vascular endothelial growth factor B is a major regulator of energy metabolism. Issue 3 (March 2020) - Chen, Yang; Zhao, Mingyue; Wang, Chenhao; Wen, Huaizhen; Zhang, Yuntao; Lu, Mingxu; Adlat, Salah; Zheng, Tingting; Zhang, Mingjiao; Li, Dan; Lu, Xiaodan; Guo, Mengwei; et al.
Abstract : Excessive fat accumulation causes obesity and many diseases. Previous study demonstrates VEGFB universal knockout induces obese phenotypes including expansion of white adipose tissue, whitening of brown adipose tissue, increase of fat accumulation and reduction in energy consumption. However, roles of VEGFB in adipose tissues are not clear. In this study, we have generated a mouse model with adipose-specific VEGFB repression using CRISPR/dCas9 system ( Vegfb AdipoDown ) and investigated the roles of VEGFB in adipose development and energy metabolism. VEGFB repression induced significant changes in adipose tissue structure and function. Vegfb AdipoDown mice have larger body sizes, larger volume of white adipose tissues than its wild type littermates. Adipose-specific VEGFB repression induced morphological and functional transformation of adipose tissues toward white adipose for energy storage. Metabolic processes are broadly changed in Vegfb AdipoDown adipose tissues including carbohydrate metabolism, lipid metabolism, nucleotide metabolism and amino acid metabolism. We have demonstrated that adipose VEGFB repression can recapitulate most of the phenotypes of the whole body VEGFB knockout mouse. Intriguingly, approximately 50% VEGFB repression in adipose tissues can almost completely mimic the effects of universal Vegfb deletion, suggesting adipose VEGFB is a major regulator of energy metabolism and may be important in prevention and treatment of obesity.